COVID-19 Disease in Under-5 Children: Current Status and Strategies for Prevention including Vaccination - Anish Pillai; Anuja Nayak; Deepika Tiwari; Pratichi Kadam Pillai; Aakash Pandita; Sachin Sakharkar; Haribalakrishna Balasubramanian; Nandkishor Kabra (Vaccines, 2023)
Since the coronavirus disease (COVID-19) pandemic hit the globe in early 2020, we have steadily gained insight into its pathogenesis; thereby improving surveillance and preventive measures. In contrast to other respiratory viruses, neonates and young children infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) have a milder clinical presentation, with only a small proportion needing hospitalization and intensive care support. With the emergence of novel variants and improved testing services, there has been a higher incidence of COVID-19 disease reported among children and neonates. Despite this, the proportion of young children with severe disease has not increased. Key mechanisms that protect young children from severe COVID-19 disease include the placental barrier, differential expression of angiotensin-converting enzyme 2 (ACE-2) receptors, immature immune response, and passive transfer of antibodies via placenta and human milk. Implementing mass vaccination programs has been a major milestone in reducing the global disease burden. However, considering the lower risk of severe COVID-19 illness in young children and the limited evidence about long-term vaccine safety, the risk–benefit balance in children under five years of age is more complex. In this review, we do not support or undermine vaccination of young children but outline current evidence and guidelines, and highlight controversies, knowledge gaps, and ethical issues related to COVID-19 vaccination in young children. Regulatory bodies should consider the individual and community benefits of vaccinating younger children in their local epidemiological setting while planning regional immunization policies.